2010
DOI: 10.1111/j.1753-5131.2010.01035.x
|View full text |Cite
|
Sign up to set email alerts
|

Swimbladder inflation and its implication to the culture of marine finfish larvae

Abstract: This review examines the initial swimbladder inflation in cultured finfish larvae and the mechanisms controlling body buoyancy and the distribution of larvae during the critical early development stages. The literature suggests that the body buoyancy of larvae affects their distribution in the tank and fish with low buoyancy are likely to sink to the bottom leading to mortality. Initial swimbladder inflation occurs in a finite period of the postlarval stage and a number of biotic and abiotic factors have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
75
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 60 publications
1
75
1
1
Order By: Relevance
“…The perch is a physoclistous fish and the initial inflation of the swimbladder and the closure of the pneumatic duct occur at 6-12 dph (Eglof, 1996;Policar, Samarin, & Mélard, 2015). Woolley and Qin (2010) suggested that larvae might be especially vulnerable to changes in hydrostatic pressure during the period of swimbladder development and differentiation. Rapid changes in hydrostatic pressure might occur when larvae are caught in upwelling water flows and drawn to the surface (Woolley & Qin, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perch is a physoclistous fish and the initial inflation of the swimbladder and the closure of the pneumatic duct occur at 6-12 dph (Eglof, 1996;Policar, Samarin, & Mélard, 2015). Woolley and Qin (2010) suggested that larvae might be especially vulnerable to changes in hydrostatic pressure during the period of swimbladder development and differentiation. Rapid changes in hydrostatic pressure might occur when larvae are caught in upwelling water flows and drawn to the surface (Woolley & Qin, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Woolley and Qin (2010) suggested that larvae might be especially vulnerable to changes in hydrostatic pressure during the period of swimbladder development and differentiation. Rapid changes in hydrostatic pressure might occur when larvae are caught in upwelling water flows and drawn to the surface (Woolley & Qin, 2010). Also in nature perch larvae select habitats with minimal water flow and are sensitive to turbulences and increased water flow (Treasurer, 1990;Kratochvil et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Larval death sometimes reaches to the level of 80% (Woolley and Qin, 2010). These mass deaths are thought be connected with factors such as broodstock quality, nutrition and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…These mass deaths are thought be connected with factors such as broodstock quality, nutrition and environmental factors. Mass deaths often peak at the time of transition to exogenous feeding following the absorption of yolk sac (Woolley and Qin, 2010). Therefore, for a successful larval rearing, optimum culture conditions should be determined according to larval development stages.…”
Section: Discussionmentioning
confidence: 99%
“…Inability to inflate the swim bladder is quite a common phenomenon in larvae kept under controlled conditions (Battaglene and Talbot 1990;Ç alta 2000;Woolley and Qin 2010). However, the moment of inflating the bladder is the major and the most critical moment related to the development of larvae of many fish species.…”
Section: Discussionmentioning
confidence: 99%